Análise estrutural do setor marmorista na região metropolitana de Fortaleza - Charron, Michele Marie (2008)
The research studied the present situation of the companies of the marble sector of the region metropolitan of Fortaleza, with respect to competitive structure of the sector. Onvestigated also if the companies in the region metropolitan of the Fortaleza had perception and analyse the competiveness of the sector and looked for identify the resources and competence for a company to compete successgully in the marble sector.Based in Michael Porter with referential theory, searched to analyze the structure of market of the sector using theory of the forces, with intention to verify as the companies develop its activities and perceived these forces. Under these aspects, the mais objective this research was to analyze the competitive structure of the marble sector of the region metropolitan of the Fortaleza and as secondary objective to identify the competitive forces in the marble sector, verify if the companies in the metropolitan region of the Fortaleza had perception and analyse the competitiveness of the sector and identify the resources and competence for a company with success in the marble sector. The research furing 12 months, having beginning in march 2007 with the elaboration of the questionnaire and after that definitive research during the month of January, February and march of 2008 was finished with the analyze and treatment of the collected data. The questionnaire was structuralized on the bases of the sacle of Liket the analyse of results was made with the use of descriptive statistics through relative frequency in percentage. For storage, verification and treatment of the data was used the Excel Office 2000.